Tourette syndrome research highlights from 2021 [version 2; peer review: 2 approved] - Per Andrén; Nanette Marinette Debes; Keisuke Ueda; Virginie Czernecki; Cécile Delorme; Natalia Szejko; Cyril Atkinson-Clement; Kevin Black; Andreas Hartmann (F1000Research, 2022)
We summarize selected research reports from 2021 relevant to Tourette syndrome that the authors consider most important or interesting. The authors welcome article suggestions and thoughtful feedback from readers.